Biomarkers of premature atherosclerosis. - Kampoli, A; Tousoulis, D; Antoniades, C; Siasos, G; Stefanadis, C (2009)
C-reactive protein (CRP) is an acute phase protein and a biochemical marker with important prognostic value for cardiovascular events. Interleukins IL-1 and IL-6 are implicated in the pathogenesis of atherosclerosis and are associated with CRP. Apolipoproteins ApoA-I and ApoB are the main lipid metabolic markers implicated in the development and progression of atherosclerosis. Fibrinogen has also been proposed to be a major independent risk factor for cardiovascular events. Because premature atherosclerosis precedes the development of cardiovascular disease, identification of the associated biomarkers is of great importance. However, further studies will be needed to determine whether or not these markers are useful predictors of future cardiovascular events. Here, we review the roles of specific biomarkers that have been implicated in premature atherosclerosis.